Nanoelectronics, nanophotonics, and quantum technologies - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, Haifeng (Selected topics in electornics and systems, 2025)
Keywords: Field (mathematics); Quantum; Quantum computer; Quantum dot; Quantum entanglement; Quantum technology; dept.phy

Energy independence of the Collins asymmetry in p ↑ p collisions - STAR Collaboration (Physical Review Letters, 2025)
The STAR experiment reports new, high-precision measurements of the transverse single-spin asymmetries for π^{±} within jets, namely the Collins asymmetries, from transversely polarized p^{↑}p collisions at sqrt[s]=510 GeV. The energy-scaled distribution of jet transverse momentum, x_{T}=2p_{T,jet}/sqrt[s], shows a remarkable consistency for Collins asymmetries of π^{±} in jets between sqrt[s]=200 GeV and 510 GeV. This indicates that the Collins asymmetries are nearly energy independent, with, at most, a very weak scale dependence in p^{↑}p collisions. These results extend to high-momentum scales (Q^{2}≤3400 GeV^{2}) and enable unique tests of evolution and universality in the transverse-momentum-dependent formalism, thus providing important constraints for the Collins fragmentation functions.
Keywords: Asymmetry; Consistency (knowledge bases); Fragmentation (computing); High energy; Independence (probability theory); Polarization (electrochemistry); Transverse plane; Universality (dynamical systems); dept.phy

Interface-Induced Polarization and Inhibition of Ferroelectricity in Epitaxial SrTiO3/Si - Kolpak, A.M.; Walker, F.J.; Reiner, J.W.; Segal, Y.; Su, D.; Sawicki, M.S.; Broadbridge, C.C.; Zhang, Z.; Zhu, Y.; Ahn, C.H.; Ismail-Beigi, S. (Handbook Of Molecular Beam Epitaxy Of Oxide Materials (In 3 Volumes), 2025)
We use SrTiO3/Si as a model system to elucidate the effect of the interface on ferroelectric behavior in epitaxial oxide films on silicon. Using both first-principles computations and synchrotron x-ray diffraction measurements, we show that structurally imposed boundary conditions at the interface stabilize a fixed (pinned) polarization in the film but inhibit ferroelectric switching. We demonstrate that the interface chemistry responsible for these phenomena is general to epitaxial silicon-oxide interfaces, impacting on the design of silicon-based functional oxide devices. © 2026 by World Scientific Publishing Co. Pte. Ltd.
Keywords: Antiferroelectricity; Epitaxy; Ferroelectricity; Induced polarization; Polarization (electrochemistry); dept.phy

Characterizing TESS-identified Quadruple- and Higher-order Eclipsing Binaries. I. Speckle Imaging with DSSI and HRCam - Majewski, Steven; Davidson, James; Wilson, Robert; Horch, Elliott; McKee, P.; Fagan, Evan; Hartwell, Gary; Kostov, Veselin; Adams, C.; Sutherland, Torrie; Tokovinin, Andreï; Wilson, John (The Astrophysical Journal, 2025)
Abstract NASA’s TESS mission has unveiled a plethora of eclipsing binaries (EBs), among them hundreds of triples and higher-order, hierarchical systems. These complex targets require follow-up observations to enable full characterization of system architectures and identify the most compact multiples expected to undergo the most dramatic dynamical evolution. We report first results from a long-term effort to perform such follow-up, focusing here on multiband speckle imaging of a majority (57) of the sample of 97 quadruple- and higher-order eclipsing binaries (Q+EBs) identified via TESS light curves by V. B. Kostov et al. Diffraction-limited imaging with the Differential Speckle Survey Instrument on the Astrophysical Research Consortium 3.5 m telescope and HRCam on the Southern Astrophysical Research 4.1 m telescope reveals nearly 60% of the 57 to resolve into two sources separated by ≥0 . ″ 03. For these partly resolved systems, we report derived characteristics (e.g., relative position angle, angular separation, and magnitude differences in multiple passbands) from the speckle imaging. We find those Q+EBs partly resolved with 4 m class telescopes to have significantly inflated Gaia parallax errors and large Gaia renormalized unit weight errors, particularly for systems with separations comparable to Gaia’s resolution limit (∼0 . ″ 6). For unresolved systems we report upper limits on angular and linear projected separations. We find two partly resolved Q+EBs with wide linear separations having eclipse timing variations that are therefore candidates of higher-than-quadruple multiplicity. Finally, we demonstrate how speckle imaging of resolved Q+EBs during an eclipse can clarify which speckle-resolved Q+EB subsystem is associated with a particular set of TESS eclipses.
Keywords: Angular resolution (graph drawing); Astrometry; Eclipse; Parallax; Speckle imaging; Speckle pattern; Telescope; dept.phy

Nanoelectronics, Nanophotonics, And Quantum Technologies: Devices And Applications - Jain, Faquir C.; Broadbridge, C.; Gherasimova, M.; Tang, Hong (World Scientific, 2025)
This timely compendium provides state-of-the-art articles covering research areas in Nanoelectronics, Nanophotonics and Quantum Technologies.Composed of contributions by renowned researchers from both the academia and industry, this useful reference text broadly illustrates relevant aspects of high-performance materials and emerging quantum and nanoscale devices for implementing high-speed electronic systems.
Keywords: Computers / Quantum Computing; Technology & Engineering / Nanotechnology & MEMS; dept.phy

Mass-luminosity anomalies: Plausible evidence of recent stellar interaction in the extraordinary blue straggler S1082 - Quitral-Pierart, Amanda; Leigh, Nathan; Mathieu, Robert; Latham, David; Sandquist, Eric; Horch, Elliott (Astronomy and Astrophysics, 2025)
Context. We present an observational and theoretical study of the complex stellar system S1082 in the open cluster M67. This system consists of at least four stars: a blue straggler in a 1.07-day eclipsing binary with a main sequence star (binary A) and another blue straggler in a 1185-day orbit with an unknown companion (binary B). Aims. We analyzed observational data to obtain the orbital and stellar parameters of the components of the eclipsing system. We then explored mass transfer and dynamical encounter scenarios that could explain the derived properties of all of the components of S1082. Methods. We combined high-precision photometry from K2 and TESS with archival light curves, new radial-velocity measurements, and speckle imaging to refine the orbital and physical parameters of the system. To explore the formation pathways, we conducted binary evolution simulations with MESA and dynamical scattering experiments with FEWBODY, followed by a tidal evolution modeling procedure. Results. Our revised radial-velocity solutions yield significantly changed dynamical masses for binary A, reducing the tension with the cluster turnoff mass compared to previous studies. Speckle imaging shows two resolved components separated by 390 AU in projection and, in combination with the two spectroscopic orbits, this is suggestive of a hierarchical quadruple configuration. Our results suggest that the two blue stragglers formed separately, with later dynamical encounters assembling the present configuration. This work underscores the importance of stellar dynamics in shaping the evolution of complex stellar systems within cluster environments such as M67.
Keywords: Binary number; Binary star; Blue straggler; Blue stragglers; Cluster (spacecraft); Open clusters and associations: individual: M67; Photometry (optics); Speckle imaging; Star cluster; Stars: individual: S1082; Stellar evolution; Stellar mass; dept.phy

Erratum: Disappearance of partonic collectivity in √ sNN = 3 GeV Au+Au collisions at RHIC (Physics Letters B, (2022), 827, 137003) - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN = 3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2025 The Authors.
Keywords: Baryonic interactions; Collectivity; High baryon density; NCQ scaling; STAR experiment; dept.phy

Temperature measurement of Quark-Gluon plasma at different stages - STAR Collaboration (Nature Communications, 2025)
In a Quark-Gluon Plasma (QGP), the fundamental building blocks of matter, quarks and gluons, are under extreme conditions of temperature and density. A QGP could exist in the early stages of the Universe, and in various objects and events in the cosmos. The thermodynamic and hydrodynamic properties of the QGP are described by Quantum Chromodynamics (QCD) and can be studied in heavy-ion collisions. Despite being a key thermodynamic parameter, the QGP temperature is still poorly known. Thermal lepton pairs (e+e− and μ+μ−) are ideal penetrating probes of the true temperature of the emitting source, since their invariant-mass spectra suffer neither from strong final-state interactions nor from blue-shift effects due to rapid expansion. Here we measure the QGP temperature using thermal e+e− production at the Relativistic Heavy Ion Collider (RHIC). The average temperature from the low-mass region (in-medium ρ0 vector-meson dominant) is (2.01 ± 0.23) × 1012 K, consistent with the chemical freeze-out temperature from statistical models and the phase transition temperature from Lattice QCD. The average temperature from the intermediate mass region (above the ρ0 mass, QGP dominant) is significantly higher at (3.25 ± 0.60) × 1012 K. This work provides essential experimental thermodynamic measurements to map out the QCD phase diagram and understand the properties of matter under extreme conditions. © The Author(s) 2025.
Keywords: Measure (data warehouse); Phase diagram; Plasma; Quantum chromodynamics; Quark–gluon plasma; Temperature measurement; Thermal; Transition temperature; Work (physics); dept.phy

Measurements of ϒ states production in p + p collisions at √s = 500 GeV with STAR: Cross sections, ratios, and multiplicity dependence - STAR Collaboration (Physical Review D, 2025)
We report measurements of ϒ(1S), ϒ(2S) and ϒ(3S) production in p + p collisions at √s = 500 GeV ffiffi by the STAR experiment in year 2011, corresponding to an integrated luminosity Lint = 13 pb−1. The results provide precise cross sections, transverse momentum (pT) and rapidity (y) spectra, as well as cross section ratios for pT < 10 GeV=c and |y| < 1. The dependence of the ϒ yield on charged particle multiplicity has also been measured, offering new insights into the mechanisms of quarkonium production. The data are compared to various theoretical models: the color evaporation model (CEM) accurately describes the ϒ(1S) production, while the color glass condensate + nonrelativistic quantum chromodynamics (CGC + NRQCD) model overestimates the data, particularly at low pT. Conversely, the color singlet model (CSM) underestimates the rapidity dependence. These discrepancies highlight the need for further development in understanding the production dynamics of heavy quarkonia in high-energy hadronic collisions. The trend in the multiplicity dependence is consistent with CGC/saturation and string percolation models or ϒ production happening in multiple parton interactions modeled by PYTHIA8. © 2025 American Physical Society
Keywords: Algorithm; Mathematics; dept.phy

Precision measurement of the longitudinal double-spin asymmetry for dijet production at intermediate pseudorapidity ffiffi in polarized pp collisions at √s = 200 GeV - STAR Collaboration (Physical Review D, 2025)
The STAR Collaboration reports precise measurements of the longitudinal double-spin asymmetry, ALL, for dijet production with at least one jet at intermediate pseudorapidity 0.8 < ηjet < 1.8 in polarized proton-proton collisions at a center-of-mass energy of 200 GeV. This study explores partons scattered with a longitudinal momentum fraction (x) from 0.01 to 0.5, which are predominantly characterized by interactions between high-x valence quarks and low-x gluons. The results are in good agreement with previous measurements at 200 GeV with improved precision and are found to be consistent with the predictions of global analyses that find the gluon polarization to be positive. In contrast, the negative gluon polarization solution from the JAM Collaboration is found to be strongly disfavored. © 2025 American Physical Society
Keywords: Asymmetry; Computer science; Particle physics; Physics; Production (economics); Pseudorapidity; Spin (aerodynamics)

Hyperon global polarization in isobar Ru+Ru and Zr+Zr collisions at sNN=200GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
The polarization of Λ , Λ ¯ , Ξ − , and Ξ ¯ + hyperons along the angular momentum of the system has been measured in isobar collisions of Ru+Ru and Zr+Zr at s N N = 200 GeV with the STAR detector at RHIC. The polarization dependence on collision centrality exhibits an increasing trend in more peripheral collisions. Λ and Λ ¯ polarization dependence on the transverse momentum and pseudorapidity have been investigated, but no significant dependence was observed. The polarizations of Λ and Λ ¯ are found to be consistent with each other, indicating little contribution of the spin-magnetic coupling to the measured polarization. Comparison to previously measured polarization in Au+Au collisions show no obvious system size dependence. The results are qualitatively consistent with hydrodynamic calculations including contributions from shear-induced polarization and thermal vorticity. For the first time in heavy-ion collisions, the dependence of the global polarization on the hyperon’s emission azimuthal angle relative to the second-order event plane has been measured, indicating stronger polarization for the in-plane emitted hyperons at the level of 2.4 σ significance in 20–50 % centrality. The Ξ hyperon polarization measurements via polarization transfer analysis yield finite positive values with 2.9 σ significance in 20–50 % centrality, slightly larger compared to the inclusive Λ polarization. © 2025 The Authors.
Keywords: Global polarization; Hyperon; Vorticity; dept.phy

Precision Measurement of Net-Proton-Number Fluctuations in Au+Au Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
We report precision measurements on cumulants (C_{n}) and factorial cumulants (κ_{n}) of (net) proton number distributions up to fourth order in Au+Au collisions over center-of-mass energies sqrt[s_{NN}]=7.7-27  GeV from phase II of the Beam Energy Scan program at RHIC. (Anti)protons are selected at midrapidity (|y|<0.5) within a transverse momentum range of 0.4<p_{T}<2.0  GeV/c. Relative to various noncritical-point model calculations and peripheral collision 70%-80% data, the net proton C_{4}/C_{2} measurement in 0%-5% collisions shows a minimum around 19.6 GeV for significance of deviation at ∼2-5σ. A minimum in C_{4}/C_{2} with respect to a noncritical baseline is expected to be a characteristic feature of the signature associated with a critical point in the QCD phase diagram. In addition, deviations from noncritical baselines around the same collision energy region are also seen in proton factorial cumulant ratios, especially in κ_{2}/κ_{1} and κ_{3}/κ_{1}. Dynamical model calculations including a critical point are called for in order to understand these precision measurements.
Keywords: Net (polyhedron); Nuclear physics; Physics; Proton; dept.phy

HST Proper Motions of Andromeda V and Andromeda VI - Casetti-Dinescu, Dana I.; Pawlowski, Marcel S.; Girard, Terrence M.; Kanehisa, Kosuke Jamie; Martone, Max; Petroski, Alexander (Astrophysical Journal, 2025)
We measure the absolute proper motions of Andromeda V (And V) and Andromeda VI/Pegasus (And VI) dwarf galaxies, satellites of M31 located near its galactic plane. And VI is located the farthest from M31 among the six satellites with currently measured proper motions. A combination of Advanced Camera for Surveys/wide filed channel (WFC) and WFPC2 exposures is utilized, spanning a 20 yr time baseline. The WFPC2 exposures are processed using a recently developed deep-learning centering procedure as well as the most up-to-date astrometric calibration of the camera. We use on the order of 100 background galaxies per satellite to determine the correction to absolute proper motion. For And V, we obtain an absolute proper motion of (μα, μδ)And V= (26.1 ± 21.5 , − 74.2 ± 19.1) μ as yr−1. For And VI, we obtain an absolute proper motion of (μα, μδ)And VI= (− 1.6 ± 12.3 , − 52.6 ± 11.2) μ as yr−1. Orbit integrations and analyses are made for these two Andromeda satellites using two estimates of both the mass and proper motion of M31. It is found that And V has an orbit consistent within errors with alignment with M31’s disk and counter orbiting it, although this alignment is not well constrained. And VI’s orbit is better determined and is very much consistent with coorbiting with M31’s disk. While currently at a distance of ∼280 kpc from M31, And VI will remain beyond a distance of ∼90 kpc from M31, thus experiencing low tidal influence compared to the other M31 satellites with known orbits. Both satellites are determined to be well-bound to M31. © 2025. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy

Measurement of Two-Point Energy Correlators within Jets in p+p Collisions at sqrt[s]=200 GeV - STAR Collaboration (Physical review letters, 2025)
Hard-scattered partons ejected from high-energy proton-proton collisions undergo parton shower and hadronization, resulting in collimated collections of particles that are clustered into jets. A substructure observable that highlights the transition between the perturbative and nonperturbative regimes of jet evolution in terms of the angle between two particles is the two-point energy correlator (EEC). In this Letter, the first measurement of the EEC at RHIC is presented, using data taken from 200 GeV p+p collisions by the STAR experiment. The EEC is measured both for all the pairs of particles in jets and separately for pairs with like and opposite electric charges. These measurements demonstrate that the transition between perturbative and nonperturbative effects occurs within an angular region that is consistent with expectations of a universal hadronization regime that scales with jet momentum for a given initiator flavor. Additionally, a deviation from Monte Carlo predictions at small angles in the charge-selected sample could result from mechanics of hadronization not fully captured by current models.
Keywords: Collimated light; Hadronization; Jet (fluid); Momentum (technical analysis); Monte Carlo method; Observable; Parton; Parton shower; Substructure; dept.phy

Onset of Constituent Quark Number Scaling in Heavy-Ion Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
Partonic collectivity is one of the necessary signatures for the formation of quark-gluon plasma in high-energy nuclear collisions. Number of constituent quarks (NCQ) scaling has been observed for hadron elliptic flow v_{2} in top energy nuclear collisions at the Relativistic Heavy Ion Collider and the LHC, and this has been theoretically suggested as strong evidence for partonic collectivity. In this Letter, a systematic analysis of v_{2} of π^{±}, K^{±}, K_{S}^{0}, p, and Λ in Au+Au collisions at sqrt[s_{NN}]=3.2, 3.5, 3.9, and 4.5 GeV, with the STAR experiment at the Relativistic Heavy Ion Collider, is presented. NCQ scaling is markedly violated at 3.2 GeV, consistent with a hadronic-interaction dominated equation of state. However, as the collision energy increases, a gradual evolution to NCQ scaling is observed. This beam-energy dependence of v_{2} for all hadrons studied provides evidence for the onset of dominant partonic interactions by sqrt[s_{NN}]=4.5  GeV.
Keywords: Heavy ion; Ion; Nuclear physics; Particle physics; Physics; Quark; Scaling; Scaling law; dept.phy

The fire blight pathogen Erwinia amylovora enters apple leaves through naturally occurring wounds from the abscission of trichomes - Millett, Felicia; Standish, James; Scanley, Jules; Miller, Katelyn; Inguagiato, John; Zuverza‐Mena, Nubia; Abril, Maritza; Robinson, Victoria; Li, Yan; Sundin, George; Zeng, Quan (The Plant Journal, 2025)
The plant epidermis is a single layer of cells covering all plant organs. How pathogens overcome this barrier and enter plants is an important aspect of plant-pathogen interactions. For bacterial plant pathogens, known entry points include natural openings, such as stomata, hydathodes, and mechanical injuries caused by insect feeding, wind damage, or hailstorms. Here, we report that the fire blight pathogen Erwinia amylovora enters apple leaves through naturally occurring wounds caused by the abscission of trichomes during the course of leaf development. Through macroscopic and microscopic observations, we depicted a clear invasion path for E. amylovora cells, from epiphytic growth on glandular trichomes (GT) and non-glandular trichomes (NT) to entry through wounds caused by abscised trichomes, into the epithem, and subsequent spread through xylem. We further observed that GT and NT undergo an abscission process, and that the amount of naturally occurring wounds during abscission is associated with the increase in E. amylovora population. Key genes important for the colonization of GT and NT were identified. The contribution of the type III secretion system and amylovoran biosynthesis during GT colonization was validated. Our findings propose a novel host entry mechanism of plant pathogenic bacteria through naturally occurring wounds during the abscission of plant surface structures.
Keywords: Abscission; Blight; Colonization; Erwinia; Erwinia amylovora; Fire blight; Trichome; abscission; dept.phy; fire blight; host entry points; trichomes; type III secretion system

Effect of binder concentration on ternary MnO2/CuS/reduced graphene oxide material for supercapacitor applications - Chaudhary, Manika; Oyelola, Lekan; Glidden, Thomas; Broadbridge, C.; LeMaire, Peter; Sharma, Rakesh; Singh, Vinamrita; Sahi, Vikhyat; Singhal, Rahúl (Journal of Solid State Electrochemistry, 2025)
Keywords: Capacitance; Chemical engineering; Chemistry; Electrochemistry; Electrode; Energy storage; Graphene; Inorganic chemistry; Materials science; Metallurgy; Nanotechnology; Oxide; Physical chemistry; Supercapacitor; Synthesis; Ternary operation; Thermodynamics; X-ray diffraction; dept.phy

Photon counting in stellar intensity interferometry: current status and future prospects - Horch, Elliott P. (Advanced Photon Counting Techniques XIX, 2025)
Intensity interferometry, also known as the Hanbury Brown and Twiss effect, has seen significant interest in astronomy in recent years. The method involves recording timing correlations between photons received at two or more telescopes in order to derive extremely high spatial resolution information about an astronomical object, potentially including imaging stellar surfaces and other objects at unprecedented scales. This paper will briefly review the technique, discuss the performance characteristics of the of photon counters used in modern intensity interferometers, and describe opportunities for the future. As an example of photon counting with a working instrument, observing experiences with the Southern Connecticut Stellar Interferometer (SCSI), a three-station instrument using single-photon avalanche diode (SPAD) detectors, will be described. The recent lessons learned with this and other instruments in use today give a clear picture of the next steps needed to upgrade efficiency and successfully observe fainter objects. If successful, these improvements would provide a strong argument for creating situations where intensity interferometers can have baselines of one to several kilometers, which would unlock the spatial detail needed to address several exciting astrophysical questions.
Keywords: Astronomy; Current (fluid); Intensity (physics); Interferometry; Optics; Photon; Photon counting; Physics; dept.phy

The Qz5 Survey. I. How the H i Mass Density of the Universe Evolves with Cosmic Time - Oyarzún, Grecco A.; Rafelski, Marc; Christensen, Lise; Ozyurt, Fiona; Jorgenson, Regina A.; Neeleman, M.; Fumagalli, Michele; Prochaska, J. Xavier; Worseck, G.; Wisz, M. E.; Becker, George D.; López, Sebastián (The Astrophysical Journal, 2025)
We report that the neutral hydrogen (H i) mass density of the Universe (ρH i) increases with cosmic time since z ∼ 5, peaks at z ∼ 3, and then decreases toward z ∼ 0. This is the first result of Qz5, our spectroscopic survey of 63 quasars at z ≳ 5 with VLT/X-SHOOTER and Keck/ESI aimed at characterizing intervening H i gas absorbers at z ∼ 5. The main feature of Qz5 is the high resolution (R ∼ 7000–9000) of the spectra, which allows us to (1) accurately detect high column density H i gas absorbers in an increasingly neutral intergalactic medium at z ∼ 5 and (2) determine the reliability of previous ρH i measurements derived with lower resolution spectroscopy. We find five intervening damped Lyα absorbers (DLAs) at z > 4.5, which corresponds to the lowest DLA incidence rate () at z ≳ 2. We also measure the lowest ρH i at z ≳ 2 from our sample of DLAs and subDLAs, corresponding to ρH i Mpc−3 at z ∼ 5. Taking into account our measurements at z ∼ 5 and systematic biases in the DLA detection rate at lower spectral resolutions, we conclude that ρH i doubles from z ∼ 5 to z ∼ 3. From these results emerges a qualitative agreement between how the cosmic densities of H i gas mass, molecular gas mass, and star formation rate build up with cosmic time.
Keywords: dept.phy; peer-reviewed

Plant-engineered ZnO and CuO nanoparticles exhibit pesticidal activity and mitigate Fusarium infestation in soybean: A mechanistic understanding - Karmous, Inès; Elmer, Wade; Zuverza‐Mena, Nubia; Vaidya, Shital; Tlahig, Samir; Scanley, Jules; Bharadwaj, Anuja; White, Jason; Dimkpa, Christian (Plant Physiology and Biochemistry, 2025)
Keywords: Antifungal activity; Artemisia vulgaris; Biogenic copper and Zn oxide nanoparticles; Biology; Botany; Chemistry; Fusarium; Infestation; Materials science; Nanoparticle; Nanotechnology; Soybean; dept.phy; peer-reviewed